Copying machine powdered ink and preparation method thereof
By using colored resin particles, silica particles A, and strontium titanate/silica composite particles in copier toner, a stable particle structure is formed, solving the problems of unstable toner charging performance and low transfer efficiency, and achieving high-efficiency image quality stability and durability.
Patent Information
- Application Number
- CN202511176003.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2025-10-03
AI Technical Summary
The existing copier toner has unstable charging performance and low transfer efficiency during long-term use, and is prone to image quality deterioration such as gray background and hollow characters, and its durable copying performance is insufficient.
The toner is mainly composed of colored resin particles, and silica particles A and strontium titanate/silicon dioxide composite particles are added as external additives. A stable particle structure is formed through efficient mixing and processing methods, which enhances the fluidity and charge stability of the toner and improves the transfer efficiency.
The toner has good charging performance and long-term stability, which improves the transfer efficiency, avoids the deterioration of image quality such as bottom gray and hollow characters, and improves the durability of copying.
Smart Images

Figure CN120742631A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of toner, and in particular to a toner for a copier and a preparation method thereof. Background Art
[0002] The following imaging method is commonly used in imaging devices such as electrophotographic devices, electrostatic recording devices, and electrostatic printing devices: first, the surface of the photosensitive drum is charged by a device such as a charging roller or a charging screen, forming an electrostatic latent image on the photosensitive drum; then, the toner is developed on the photosensitive drum under the action of the electrostatic latent image to form a toner image; then, the toner image is transferred to a recording material such as paper; finally, the toner image is fixed by heating or other methods to obtain a copy.
[0003] In this process, the performance of the toner directly determines the quality of the copied document. To achieve excellent copying documents, the toner must have good charging properties, and this charging performance must be long-lasting and stable. Currently, the industry generally improves the charging performance of the toner by adding suitable external additives and attaching them to the surface of the colored resin particles. However, the toners used in the existing technology often experience deterioration in image quality, such as graying of the bottom and hollow characters, during long-term continuous use. Transfer efficiency is also difficult to maintain, and the durability of the copying performance needs to be further improved. Summary of the Invention
[0004] The present invention aims to overcome the defects of the prior art such as insufficient charging stability, low transfer efficiency, and easy deterioration of image quality after long-term use of toner, and provides a copier toner and a preparation method thereof. The toner has good charging performance, long-lasting and stable charging, high transfer efficiency, and will not produce image quality deterioration such as background dust and hollow characters during continuous printing, and excels in durable copying performance.
[0005] The purpose of the present invention is achieved by adopting the following technical solutions:
[0006] A first aspect of the present invention provides a toner for a copier, comprising:
[0007] Colored resin particles, wherein the amount of the colored resin particles is 95-99.8% of the total weight of the toner; wherein the colored resin particles include the following components in parts by weight: 75-90 parts of resin, 2-10 parts of colorant, 0.5-8 parts of charge regulator, and 1.5-8 parts of release agent;
[0008] External additives, the amount of external additives is 0.2-5% of the total weight of the toner;
[0009] The external additives include silica particles A, silica particles B and strontium titanate / silica composite particles; the strontium titanate / silica composite particles include strontium titanate particles and a silica shell layer coated on the surface of the strontium titanate particles, and the silica shell layer is treated with an organic silane modifier.
[0010] In the first aspect of the present invention, as an optional embodiment, the amount of the silica particles A is 0.6%-1.2% of the total weight of the toner; the amount of the silica particles B is 0.5%-1.0% of the total weight of the toner; and the amount of the strontium titanate / silicon dioxide composite particles is 0.5%-1.5% of the total weight of the toner.
[0011] In the first aspect of the present invention, as an optional embodiment, the amount of the silica particles A is 0.9% of the total weight of the toner; the amount of the silica particles B is 0.5% of the total weight of the toner; and the amount of the strontium titanate / silicon dioxide composite particles is 0.5% of the total weight of the toner.
[0012] In the first aspect of the present invention, as an optional embodiment, the average particle size of the silica particles A is 7nm-16nm, and the average particle size of the silica particles B is 30nm-50nm; in the strontium titanate / silicon dioxide composite particles, the particle size of the strontium titanate particles is 100nm-300nm, and the thickness of the silica shell is 3nm-10nm.
[0013] In the first aspect of the present invention, as an optional embodiment, the average particle size of the silica particles A is 8 nm, and the average particle size of the silica particles B is 50 nm; in the strontium titanate / silicon dioxide composite particles, the particle size of the strontium titanate particles is 150 nm, and the thickness of the silica shell is 5 nm.
[0014] In the first aspect of the present invention, as an optional embodiment, the bonding resin is one or a mixture of two or more of styrene-acrylic copolymer resin, styrene-butadiene copolymer resin, polyester resin and epoxy resin.
[0015] In the first aspect of the present invention, as an optional embodiment, the charge control agent is a positive charge control agent or a negative charge control agent; wherein the positive charge control agent is nigrosine or a quaternary ammonium salt; and the negative charge control agent is a metal chelate or a metal salt of salicylic acid.
[0016] In the first aspect of the present invention, as an optional embodiment, the release agent is low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, carnauba wax or ester wax.
[0017] In the first aspect of the present invention, as an optional embodiment, the method for preparing the strontium titanate / silicon dioxide composite particles comprises the following steps:
[0018] S10, dispersing strontium titanate particles with a particle size of 100 nm to 300 nm in an aqueous solution containing sodium lauryl sulfate;
[0019] S20, adding ammonia water and tetraethoxysilane, reacting at 38-42° C. and pH 9-10 to form a silica shell;
[0020] S30, adding a hydrophobic treatment agent, and performing hydrophobic treatment at 58-62° C. for 1.5-2.5 hours to obtain a strontium titanate / silicon dioxide particle solution;
[0021] S40, the strontium titanate / silicon dioxide particle solution is washed with deionized water, filtered, and dried at 95-105° C. to obtain strontium titanate / silicon dioxide composite particles.
[0022] In the first aspect of the present invention, as an optional embodiment, the hydrophobic treatment agent is one or a mixture of two or more of hexamethyldisilazane, trimethylsilane, trimethylchlorosilane, trimethylethoxysilane, dimethyldichlorosilane, dimethylethoxysilane, and hexamethyldisiloxane.
[0023] A second aspect of the present invention provides a method for preparing copier toner, comprising:
[0024] S100, mixing step: mixing the binder resin, colorant, charge control agent and release agent at a stirring speed of 38-42 m / s for 4-6 minutes;
[0025] S200, mixing step: mixing the mixture at 120-130° C. through a twin-screw extruder, ultrafinely grinding and then classifying to obtain semi-finished particles with a D50 of 8.0-9.0 μm;
[0026] S300, post-addition step: adding external additives to the semi-finished granules, and mixing at a stirring speed of 38-42 m / s for 1-3 minutes.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The colored resin particles of the present invention serve as the main component of the toner, wherein the resin acts as a binder, firmly bonding the colorant, charge modifier, and release agent to form a stable particle structure. During the printing process, the resin melts due to heat, allowing the toner to adhere to the paper and achieve fixation. The colorant imparts color to the toner, used to present images and text. The charge modifier controls the charging properties of the toner, allowing it to accurately adsorb to the charged areas of the photosensitive drum during electrostatic imaging, achieving image development. The release agent helps the toner to smoothly detach from equipment components (such as the photosensitive drum, fuser roller, etc.) after printing, preventing toner residue and adhesion. The external additives, silica particles A, silica particles B, and strontium titanate / silicon dioxide composite particles, are mixed with the colored resin particles to improve various properties of the toner. The silica particles can improve the fluidity and charge stability of the toner. Their small particle size and high specific surface area can form a uniform coating on the surface of the toner particles, reducing agglomeration between toner particles and enhancing the toner's dispersibility. The strontium titanate / silica composite particles possess unique electrical properties that synergize with the silica shell to enhance the transfer efficiency of toner images, enabling more efficient transfer of toner from the photosensitive drum to paper. Furthermore, the silica shell, treated with an organosilane modifier, enhances the hydrophobicity and chemical stability of the composite particles, further improving their performance in toner. As a result, the toner of the present invention exhibits excellent and stable charging properties, high transfer efficiency, and continuous printing without image quality degradation such as background dusting and hollow characters, resulting in superior duplication performance.
[0029] 2. The method for preparing copier toner of the present invention comprises: in the mixing step, a binder resin, a colorant, a charge control agent, and a release agent are mixed at a stirring speed of 38-42 m / s for 4-6 minutes. The high-speed stirring allows these ingredients to be fully and evenly mixed together, ensuring the consistency of the toner composition. In the kneading step, the mixture is kneaded in a twin-screw extruder at 120-130°C. This temperature range allows the binder resin to soften and fully blend with the other ingredients to form a uniform melt. Ultrafine grinding and classification are then performed to obtain semi-finished particles with a D50 of 8.0-9.0 μm. The appropriate particle size distribution has a significant impact on the toner's fluidity, charging performance, and transfer efficiency. In the post-addition step, an external additive is added to the semi-finished particles and mixed at a stirring speed of 38-42 m / s for 1-3 minutes. The external additive is evenly adhered to the surface of the semi-finished particles and exerts its effect of improving the toner's performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a process flow chart of a method for preparing copier toner;
[0031] Figure 2This is a process flow chart of the preparation method of strontium titanate / silicon dioxide composite particles of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described below with reference to the accompanying drawings and specific embodiments. It should be noted that, provided no conflicts exist, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments. Unless otherwise specified, the materials and equipment used in this embodiment are commercially available.
[0033] A first aspect of the present invention provides a toner for a copier, comprising:
[0034] Colored resin particles, wherein the amount of the colored resin particles is 95-99.8% of the total weight of the toner; wherein the colored resin particles include the following components in parts by weight: 75-90 parts of resin, 2-10 parts of colorant, 0.5-8 parts of charge regulator, and 1.5-8 parts of release agent;
[0035] External additives, the amount of external additives is 0.2-5% of the total weight of the toner;
[0036] The external additives include silica particles A, silica particles B and strontium titanate / silica composite particles; the strontium titanate / silica composite particles include strontium titanate particles and a silica shell layer coated on the surface of the strontium titanate particles, and the silica shell layer is treated with an organic silane modifier.
[0037] Based on the above scheme, the colored resin particles of the present invention serve as the main component of the toner, wherein the resin acts as a binder, firmly binding the colorant, charge regulator, and release agent to form a stable particle structure. During the printing process, the resin is heated and melted, allowing the toner to adhere to the paper and achieve fixation. The colorant imparts color to the toner, used to present images and text. The charge regulator controls the charging properties of the toner, allowing it to accurately adsorb to the charged area of the photosensitive drum during electrostatic imaging to achieve image development. The release agent helps the toner to smoothly detach from equipment components (such as the photosensitive drum, fuser roller, etc.) after printing, preventing toner residue and adhesion. The silica particles A, silica particles B, and strontium titanate / silicon dioxide composite particles in the external additives are mixed with the colored resin particles to improve various properties of the toner. The silica particles can improve the fluidity and charge stability of the toner. Their small particle size and high specific surface area can form a uniform coating on the surface of the toner particles, reducing agglomeration between toner particles and enhancing the dispersibility of the toner. The strontium titanate / silica composite particles possess unique electrical properties that synergize with the silica shell to enhance the transfer efficiency of toner images, enabling more efficient transfer of toner from the photosensitive drum to paper. Furthermore, the silica shell, treated with an organosilane modifier, enhances the hydrophobicity and chemical stability of the composite particles, further improving their performance in toner. As a result, the toner of the present invention exhibits excellent and stable charging properties, high transfer efficiency, and continuous printing without image quality degradation such as background dusting and hollow characters, resulting in superior duplication performance.
[0038] In the first aspect of the present invention, as an optional embodiment, the amount of the silica particles A is 0.6%-1.2% of the total weight of the toner; the amount of the silica particles B is 0.5%-1.0% of the total weight of the toner; and the amount of the strontium titanate / silicon dioxide composite particles is 0.5%-1.5% of the total weight of the toner.
[0039] In the first aspect of the present invention, as an optional embodiment, the amount of the silica particles A is 0.9% of the total weight of the toner; the amount of the silica particles B is 0.5% of the total weight of the toner; and the amount of the strontium titanate / silicon dioxide composite particles is 0.5% of the total weight of the toner.
[0040] In the first aspect of the present invention, as an optional embodiment, the average particle size of the silica particles A is 7nm-16nm, and the average particle size of the silica particles B is 30nm-50nm; in the strontium titanate / silicon dioxide composite particles, the particle size of the strontium titanate particles is 100nm-300nm, and the thickness of the silica shell is 3nm-10nm.
[0041] In the first aspect of the present invention, as an optional embodiment, the average particle size of the silica particles A is 8 nm, and the average particle size of the silica particles B is 50 nm; in the strontium titanate / silicon dioxide composite particles, the particle size of the strontium titanate particles is 150 nm, and the thickness of the silica shell is 5 nm.
[0042] In the first aspect of the present invention, as an optional embodiment, the bonding resin is one or a mixture of two or more of styrene-acrylic copolymer resin, styrene-butadiene copolymer resin, polyester resin and epoxy resin.
[0043] In the first aspect of the present invention, as an optional embodiment, the colorant can use phthalocyanine blue pigments and their derivatives and anthraquinone pigments, such as CI Pigment Blue 15:1, 15:3, 15:4, etc.; magenta colorants can use azo pigments such as monoazo pigments and disazo pigments, as well as condensed polycyclic pigments, such as CI Pigment Red 122, 146, 269, etc.; yellow colorants can use azo pigments such as monoazo pigments and disazo pigments, as well as condensed polycyclic pigments, such as CI Pigment Yellow 74, 155, 180, 185, etc. The above colorants can be used alone or in combination of two or more.
[0044] In the first aspect of the present invention, as an optional embodiment, the charge control agent is a positive charge control agent or a negative charge control agent; wherein the positive charge control agent is nigrosine or a quaternary ammonium salt; and the negative charge control agent is a metal chelate or a metal salt of salicylic acid.
[0045] In the first aspect of the present invention, as an optional embodiment, the release agent is low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, carnauba wax or ester wax.
[0046] Please refer to Figure 2 In the first aspect of the present invention, as an optional embodiment, the method for preparing the strontium titanate / silicon dioxide composite particles comprises the following steps:
[0047] S10, dispersing strontium titanate particles with a particle size of 100 nm to 300 nm in an aqueous solution containing sodium lauryl sulfate;
[0048] S20, adding ammonia water and tetraethoxysilane, reacting at 38-45° C. and pH 9-10 to form a silica shell;
[0049] S30, adding a hydrophobic treatment agent, and performing hydrophobic treatment at 58-62° C. for 1.5-2.5 hours to obtain a strontium titanate / silicon dioxide particle solution;
[0050] S40, the strontium titanate / silicon dioxide particle solution is washed with deionized water, filtered, and dried at 95-105° C. to obtain strontium titanate / silicon dioxide composite particles.
[0051] In a sol-gel reaction, TEOS (tetraethoxysilane) and ammonia react primarily to form silicon dioxide through hydrolysis and condensation. The gel formation process can be controlled by adjusting parameters such as ammonia concentration and temperature.
[0052] The reaction mechanism is as follows:
[0053] Hydrolysis reaction: The ethoxy group in the TEOS molecule reacts with water to generate silanol (Si-OH) and ethanol. The reaction formula is:
[0054] Si(OC2H5)4+H2O→Si(OC2H5)3OH+C2H5OH;
[0055] In this stage, ammonia acts as a catalyst to promote hydrolysis.
[0056] Condensation reaction: The generated silanol groups are further dehydrated to form a three-dimensional network structure.
[0057] The reaction formula is: 2Si-OH→Si-O-Si+H2O;
[0058] The concentration of ammonia directly affects the pH of the solution (optimal pH range is 9-10), which in turn regulates the condensation rate. The temperature should be controlled below 45°C; exceeding this temperature will result in a loose gel structure.
[0059] Gel time: Gel time can be controlled by adjusting the amount of ammonia water.
[0060] The preparation method of the strontium titanate / silicon dioxide composite particles comprises the following steps:
[0061] S10, adding 50 g of strontium titanate particles with a particle size of 150±3 nm and 20 g of sodium lauryl sulfate (surfactant) to 435 ml of deionized water, and stirring and dispersing them at a speed of 3000 rpm using a high-speed shear disperser for 0.5 h;
[0062] S20, add 19 ml of ammonia water and 420 ml of ethanol solution, continue stirring for 0.5 h, add 12.6 ml of TEOS, react at 40° C. for 3 hours, and obtain a solution of strontium titanate particles uniformly coated with silica.
[0063] S30, adding 3 ml of trifluoropropylsilane, and reacting at 60° C. for 2 h to obtain a hydrophobic strontium titanate silica particle solution.
[0064] S40, washing with deionized water, filtering, and drying at 100° C. to obtain strontium titanate-silica composite particles.
[0065] The average particle size of the strontium titanate / silicon dioxide composite particles was determined by a laser particle size analyzer to be 155±3 nm, the core particle size of strontium titanate to be 150 nm±3 nm, and the thickness of the silicon dioxide shell to be 5 nm.
[0066] In the first aspect of the present invention, as an optional embodiment, the hydrophobic treatment agent is one or a mixture of two or more of hexamethyldisilazane, trimethylsilane, trimethylchlorosilane, trimethylethoxysilane, dimethyldichlorosilane, dimethylethoxysilane, and hexamethyldisiloxane.
[0067] When the strontium titanate / silica composite particles are hydrophobized, these silane groups react chemically with the hydroxyl groups on the surface of the silica shell to form silicon-oxygen bonds, introducing hydrophobic groups into the silica shell surface. This hydrophobization treatment changes the surface properties of the silica shell from hydrophilic to hydrophobic, reducing the composite particles' adsorption of water, improving their dispersibility and stability in the toner system, and enhancing their compatibility with other toner components.
[0068] Please refer to Figure 1 The second aspect of the present invention provides a method for preparing copier toner, comprising:
[0069] S100, mixing step: mixing the binder resin, colorant, charge control agent and release agent at a stirring speed of 38-42 m / s for 4-6 minutes;
[0070] S200, mixing step: mixing the mixture at 120-130° C. through a twin-screw extruder, ultrafinely grinding and then classifying to obtain semi-finished particles with a D50 of 8.0-9.0 μm;
[0071] S300, post-addition step: adding external additives to the semi-finished granules, and mixing at a stirring speed of 38-42 m / s for 1-3 minutes.
[0072] The following are some embodiments listed in this application, and the application is further illustrated by the following embodiments.
[0073] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used can be purchased through conventional commercial channels unless otherwise specified.
[0074] The high-speed mixer was manufactured by Nanjing White Bear Machinery Co., Ltd., model H-100L, and the co-rotating twin-screw extruder was manufactured by Nanjing Chengmeng Machinery Co., Ltd., model TSH-25. The air jet mill was manufactured by Shanghai Chemical Machinery Plant No. 3, model 100.
[0075] Example 1
[0076] A toner for a photocopier, comprising:
[0077] Colored resin particles, wherein the amount of the colored resin particles is 98.4% of the total weight of the toner; wherein the colored resin particles include the following components in parts by weight: 89 parts of resin, 6 parts of colorant, 3 parts of charge regulator, and 2 parts of release agent; see Table 1 for details;
[0078] Table 1
[0079] Reagents Element parts by weight resin polyester resin 89 copies; Colorants Black pigment 6 servings; Charge regulator Zinc salicylate complex 3 servings; release agent Polyethylene wax 2 servings;
[0080] External additives, the amount of external additives is 1.6% of the total weight of the toner;
[0081] The external additive comprises silica particles A, silica particles B, and strontium titanate / silica composite particles; the strontium titanate / silica composite particles comprise strontium titanate particles and a silica shell layer coated on the surface of the strontium titanate particles, wherein the silica shell layer is treated with an organic silane modifier; the amount of silica particles A is 0.6% of the total weight of the toner, the amount of silica particles B is 0.5% of the total weight of the toner, and the amount of strontium titanate / silica composite particles is 0.5% of the total weight of the toner;
[0082] The preparation method of the strontium titanate / silicon dioxide composite particles comprises the following steps:
[0083] S10, adding 50 g of strontium titanate particles with a particle size of 150 nm and 20 g of sodium lauryl sulfate (surfactant) to 435 ml of deionized water, and stirring and dispersing them at a speed of 3000 rpm using a high-speed shear disperser for 0.5 h;
[0084] S20, add 19 ml of ammonia water and 420 ml of ethanol solution, continue stirring for 0.5 h, add 12.6 ml of TEOS, react at 40° C. for 3 hours, and obtain a solution of strontium titanate particles uniformly coated with silica.
[0085] S30, adding 3 ml of trifluoropropylsilane, and reacting at 60° C. for 2 h to obtain a hydrophobic strontium titanate silica particle solution.
[0086] S40, washing with deionized water, filtering, and drying at 100° C. to obtain strontium titanate-silica composite particles.
[0087] On the basis of the above method, the average particle size of the strontium titanate / silicon dioxide composite particles was determined to be 155nm, the strontium titanate core particle size was 150nm, and the silica shell thickness was 5nm by laser diffraction particle size analyzer. The silica shell thickness depends on the amount of TEOS used. The more TEOS used, the more silica that can be deposited and the thicker the shell. Therefore, while fixing the strontium titanate concentration, the TEOS amount was adjusted proportionally. In step S20, 5.04ml of TEOS was added to obtain strontium titanate / silicon dioxide composite particles with a core of 150nm and a shell of 2nm. In step S20, 30.24ml of TEOS was added to obtain strontium titanate / silicon dioxide composite particles with a core of 150nm and a shell of 12nm.
[0088] A method for preparing copier toner, comprising:
[0089] S100, mixing step: mixing the binder resin, colorant, charge control agent and release agent at a stirring speed of 40 m / s for 5 minutes;
[0090] S200, mixing step: mixing the mixture at 250° C. through a twin-screw extruder, ultrafinely grinding and classifying to obtain semi-finished particles with a D50 of 8.5 μm;
[0091] S300, post-addition step: adding external additives to the semi-finished granules, and mixing at a stirring speed of 40 m / s for 2 minutes.
[0092] In this embodiment, the polyester resin is FC1565, a polyester resin produced by Mitsubishi Chemical Corporation of Japan. The black pigment is MA100, a pigment produced by Mitsubishi Corporation of Japan. The zinc salicylate complex is DL-N24M, a zinc salicylate complex produced by Hubei Dinglong Chemical Co., Ltd. The polyethylene wax is POLYWAX 2000, a polyethylene wax produced by Baker Hughes Company of the United States.
[0093] Experiments 1 to 20 were conducted based on Example 1, with the use of different external additives.
[0094] Silica A and Silica B:
[0095] WACKER's model H3004 has a particle size of 8nm; model H2000T has a particle size of 12nm; Cabot's model TG6110 has a particle size of 23nm; Evonik Degussa's model NA380SH has a particle size of 6nm;
[0096] The model H05TM of WACKER has a particle size of 50nm; the model RY50 of Evonik Degussa has a particle size of 40nm; the model KSN005L of TAYCA CORPORATION has a particle size of 80nm, and the model TG-C19110 has a particle size of 115nm.
[0097] Table 2
[0098]
[0099]
[0100] Printing tests were conducted on a Sharp MX2600N color copier at 25°C and 70% humidity (26 pages / minute for color printing and 26 pages / minute for copying, with image enhancement up to 2400 dpi). 10,000 pages were printed using the ISO / IEC 19752 standard monochrome print test page with 5% coverage. Image density, base gray, and toner transfer efficiency were measured at the start of page 0 and page 10,000 as follows.
[0101] 1. Image density (ID)
[0102] The test toner was used to print a comprehensive test plate on a Sharp MX2600N color copier, and the actual area image density was measured using an X-rite528X / LP reflection densitometer. The test results are expressed as follows: ◎: image density ≥1.4; ○: 1.4<image density ≤1.3; △: 1.3<image density ≤1.2; x: image density ≤1.1.
[0103] 2. Bottom ash
[0104] This value reflects the developing density in the non-developing area of the copy (print). Generally, the lower the better. The test results are expressed as follows: ◎: Base ash < 0.01; ○: 0.01 ≤ Base ash < 0.02; △: 0.02 ≤ Base ash < 0.03; x: Base ash ≥ 0.03.
[0105] 3. Toner transfer rate
[0106] The toner transfer rate after 10,000 pages of the ISO / IEC19752 5% coverage monochrome printing standard test page printing test is calculated using the following formula:
[0107] Toner transfer rate = (toner consumption weight - waste toner weight) / toner consumption weight; (%)
[0108] If the toner transfer rate is ≥87%, it is marked as "◎"; if 84%≤toner transfer rate<87%, it is marked as ○; if 80%≤toner transfer rate<84% "△"; if toner transfer rate<80, it is marked as "X".
[0109] Table 3 Test results
[0110]
[0111] As can be seen from Tables 2 and 3 above, the combined use of silica particles A, silica particles B, and surface-treated strontium titanate / silica composite particles results in a toner with excellent charging performance within the range described in the present invention. Furthermore, the toner exhibits long-lasting and stable charging properties, high transfer efficiency, and continuous printing without image quality degradation such as dusting. This results in superior durable copying performance.
[0112] Table 4 Comparative carbon powder test
[0113]
[0114]
[0115] Table 5 Comparative carbon powder test results
[0116]
[0117] As can be seen from Tables 4 and 5 above, the use of silica particles A, silica particles B and surface-treated strontium titanate / silica composite particles alone or in combination, or the use of silica particles A, silica particles B and untreated strontium titanate / silica composite particles in combination, will result in low image density, gray background, and decreased toner transfer rate during continuous printing.
[0118] Example 2
[0119] A toner for a photocopier, comprising:
[0120] Colored resin particles, the amount of the colored resin particles is 98.1% of the total weight of the toner; wherein the colored resin particles include the following components in parts by weight: 90 parts of resin, 5 parts of colorant, 2 parts of charge regulator, and 3 parts of release agent; see Table 6 for details;
[0121] Table 6
[0122] Reagents Element parts by weight resin Styrene-acrylic acid copolymer resin 90 copies; Colorants Black pigment 5 servings; Charge regulator Iron azo compounds 2 servings; release agent Polyethylene wax 3 servings;
[0123] External additives, the amount of external additives is 1.9% of the total weight of the toner;
[0124] The external additives include silica particles A, silica particles B and strontium titanate / silica composite particles; the strontium titanate / silica composite particles include strontium titanate particles and a silica shell layer coated on the surface of the strontium titanate particles, and the silica shell layer is treated with an organic silane modifier.
[0125] In this embodiment, the styrene-acrylic acid copolymer resin was SMA871, produced by Tianjin Synthetic Materials Research Institute; the black pigment was MA100, produced by Mitsubishi, Japan. The iron azo compound was DL-N33, produced by Hubei Dinglong Chemical Co., Ltd.; and the polyethylene wax was POLYWAX2000, produced by Baker Hughes, USA.
[0126] The preparation method of the strontium titanate / silicon dioxide composite particles and the copier toner of this embodiment is the same as that of Example 1.
[0127] The printing test was conducted on a Sharp MX2600N color copier at a temperature of 25°C and a humidity of 70% RH.
[0128] Table 7 Specific implementation of the external additives of Example 2
[0129]
[0130] Table 8 Test results
[0131]
[0132] As can be seen from Tables 7 and 8 above, the toner uses styrene acrylic resin, and the external additives silica particles A and silica particles B are used in combination with surface-treated strontium titanate / silica composite particles. Within the range described in the present invention, the toner has good charging performance, long-lasting and stable charging, high transfer efficiency, and does not produce image quality deterioration such as bottom dusting during continuous printing, thereby excelling in durable copying performance.
[0133] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and replacements made by those skilled in the art on the basis of the present invention fall within the scope of protection required by the present invention.
Claims
1. A copier toner, characterized in that: include: Colored resin particles, wherein the amount of the colored resin particles is 95-99.8% of the total weight of the toner; wherein the colored resin particles include the following components in parts by weight: 75-90 parts of resin, 2-10 parts of colorant, 0.5-8 parts of charge regulator, and 1.5-8 parts of release agent; External additives, the amount of external additives is 0.2-5% of the total weight of the toner; The external additives include silica particles A, silica particles B and strontium titanate / silica composite particles; the strontium titanate / silica composite particles include strontium titanate particles and a silica shell layer coated on the surface of the strontium titanate particles, and the silica shell layer is treated with an organic silane modifier.
2. The copier toner according to claim 1, wherein The amount of the silicon dioxide particles A is 0.6%-1.2% of the total weight of the toner; the amount of the silicon dioxide particles B is 0.5%-1.0% of the total weight of the toner; and the amount of the strontium titanate / silicon dioxide composite particles is 0.5%-1.5% of the total weight of the toner.
3. The copier toner according to claim 2, wherein: The amount of the silicon dioxide particles A is 0.9% of the total weight of the toner; the amount of the silicon dioxide particles B is 0.5% of the total weight of the toner; and the amount of the strontium titanate / silicon dioxide composite particles is 0.5% of the total weight of the toner.
4. The copier toner according to claim 1, wherein The average particle size of the silica particles A is 7nm-16nm, and the average particle size of the silica particles B is 30nm-50nm; in the strontium titanate / silicon dioxide composite particles, the particle size of the strontium titanate particles is 100nm-300nm, and the thickness of the silica shell is 3nm-10nm.
5. The copier toner according to claim 4, wherein The average particle size of the silica particles A is 8 nm, and the average particle size of the silica particles B is 50 nm. In the strontium titanate / silicon dioxide composite particles, the particle size of the strontium titanate particles is 150 nm, and the thickness of the silica shell is 5 nm.
6. The copier toner according to claim 1, wherein The bonding resin is one or a mixture of two or more of styrene-acrylic acid copolymer resin, styrene-butadiene copolymer resin, polyester resin and epoxy resin.
7. The copier toner according to claim 1, wherein The charge control agent is a positive charge control agent or a negative charge control agent; wherein the positive charge control agent is aniline black or a quaternary ammonium salt; the negative charge control agent is a metal chelate or a metal salt of salicylic acid; and the release agent is low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, carnauba wax or ester wax.
8. The copier toner according to claim 1, wherein The preparation method of the strontium titanate / silicon dioxide composite particles comprises the following steps: S10, dispersing strontium titanate particles with a particle size of 100 nm to 300 nm in an aqueous solution containing sodium lauryl sulfate; S20, adding ammonia water and tetraethoxysilane, reacting at 38-42° C. and pH 9-10 to form a silica shell; S30, adding a hydrophobic treatment agent, and performing hydrophobic treatment at 58-62° C. for 1.5-2.5 hours to obtain a strontium titanate / silicon dioxide particle solution; S40, the strontium titanate / silicon dioxide particle solution is washed with deionized water, filtered, and dried at 95-105° C. to obtain strontium titanate / silicon dioxide composite particles.
9. The copier toner according to claim 8, wherein The hydrophobic treatment agent is one or a mixture of two or more of hexamethyldisilazane, trimethylsilane, trimethylchlorosilane, trimethylethoxysilane, dimethyldichlorosilane, dimethylethoxysilane and hexamethyldisiloxane.
10. The method for preparing copier toner according to claims 1 to 9, characterized in that: include: S100, mixing step: mixing the binder resin, colorant, charge control agent and release agent at a stirring speed of 38-42 m / s for 4-6 minutes; S200, mixing step: mixing the mixture at 120-130° C. through a twin-screw extruder, ultrafinely grinding and then classifying to obtain semi-finished particles with a D50 of 8.0-9.0 μm; S300, post-addition step: adding external additives to the semi-finished granules, and mixing at a stirring speed of 38-42 m / s for 1-3 minutes.